Longer prehospital time was not associated with mortality in major trauma. A retrospective cohort study. - Brown, E.; Tohira, Hideo; Bailey, P.; Fatovich, D.; Pereira, G.; Finn, J. (Informa Healthcare, 2018)
OBJECTIVE: To determine the association between prehospital time and outcomes in adult major trauma patients, transported by ambulance paramedics. METHODS: A retrospective cohort study of major trauma patients (Injury Severity Score >15) attended by St John Ambulance paramedics in Perth, Western Australia, who were transported to hospital between 1st January 2013 and 31st December 2016. Inverse probability of treatment weighting (IPTW) using the propensity score was performed to limit selection bias and confounding. The primary outcome was 30-day mortality and the secondary outcome was the length of hospital stay (LOS) for 30-day survivors. Multivariate logistic and log-linear regression analyses with IPTW were used to determine if prehospital time of more than the one hour (from receipt of the emergency call to arrival at hospital) or any individual prehospital time interval (response, on-scene, transport or total time) was associated with 30-day mortality or LOS. RESULTS: A total of 1,625 major trauma patients were included and 1,553 included in the IPTW sample. No significant association between prehospital time of one hour and 30-day mortality was found (adjusted odds ratio 1.10, 95% confidence interval (CI) 0.71-1.69). No association between any individual prehospital time interval and 30-day mortality was identified. In the 30-day survivors, one-minute increase of on-scene time was associated with 1.16 times (95% CI 1.03-1.31) longer LOS. CONCLUSION: Longer prehospital times were not associated with an increased likelihood of 30-day mortality in major trauma patients transported to hospital by ambulance paramedics. We found no evidence to support the hypothesis that prehospital time longer than one hour resulted in an increased risk of 30-day mortality. However, longer on-scene time was associated with longer hospital LOS (for 30-day survivors). Our recommendation is that prehospital care is delivered in a timely fashion and delivery of the patient to hospital is reasonably prompt.